Intraoperative Finding of Anomalous Circumflex Artery Origin in the Dissected Right Coronary Ostium - Mori, Makoto; Amabile, Andrea; Vallabhajosyula, Prashanth (AORTA, 2022)
Anomalous origin of the left circumflex artery is a rare anatomical variant that may present a unique challenge in emergent aortic surgery.
Keywords: anomalous; circumflex; aortic; dissection; Bentall root replacement